Legal Protection and Welfare for Private Lecturers: Addressing Sub-Minimum Wage Challenges in West Java - Ahyani, Hisam; Azmi, Naelul; Lousada, Sérgio António Neves; Huda, Miftakhul; Abduloh, Agus Yosep (Jurnal Media Hukum, 2025)
Private lecturers in Indonesia play a crucial role in higher education; however, they face significant welfare issues, particularly concerning salaries that often fall below the Regional Minimum Wage (UMK). This study aims to identify the challenges faced by private lecturers in West Java related to inadequate salaries and offer recommendations for improvement. Using a qualitative research approach, the study interviews private lecturers and analyzes employment agreements from several private universities. It also examines relevant laws and regulations, including Law Number 14 of 2005 on Teachers and Lecturers, Government Regulation Number 37 of 2009 on Lecturers, Law Number 30 of 2014 on Government Administration, and Law Number 13 of 2003 on Manpower. The findings reveal that, despite formal employment agreements, many lecturers earn less than the UMK, negatively impacting their welfare. Contributing factors include a lengthy certification process, inadequate social security, and the lack of academic ranks for many permanent lecturers. Many private lecturers are not registered with the social security program (BPJS). This study concludes that salaries below the UMK create injustice and undermine the teaching profession. Strengthening employment contracts, clarifying rights and obligations, and raising awareness about lecturers' rights are essential for improving their welfare.